FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR SISWA-SISWI KELAS X-XI DI SMA NEGERI 4 KOTA SORONG - Jenni Lilis Siagian; Irfandi Rahman (Elisabeth Health Jurnal, 2020)
Introduction: Many students learn less focus both at home and at school. The results of interviews with 10 students of class X-XI Sorong 4 Public High School, 50% said that the learning system at home is free, not noticed by parents or family members at home, if there is homework, the process is sometimes at home and not rarely done at school, after returning from school usually directly playing with school friends and neighbors. Method: This type of research is analytic descriptive with cross sectional design. The study was conducted in Sorong City High School 4 in February 2020. The population in this study were all students of class X-XI in Sorong City High School 4. The total sample of 74 people with the sampling technique is total sampling. The study was conducted using a questionnaire instrument. The data obtained were analyzed using the Pearson Product Moment test, at a 95% confidence level.Result: Based on the results of the analysis, it is known that there is an influence of parental support, intrinsic motivation and learning facilities on the learning achievement of students of the X-XI class of SMA Negeri 4, Sorong City. Discussion: Children who get full support from parents will be more motivated and motivated to study harder, while children who lack support from parents will feel that they are not useful so that the enthusiasm for learning is absent, and the desire to increase their potential is absent. Parents need to pay attention to children, especially when the child is still in adolescence, this time the child needs attention to find the identity that will take the child in the future. The intrinsic motivation of students is on average good though not good on all the questions asked. Intrinsic learning motivation of students will increase self-awareness to learn well with goals essentially, not only look good or to get attention, and this will have an impact on student achievement well and vice versa. Learning facilities can affect learning achievement, this can be seen from the teaching and learning facilities in school classrooms, tables, chairs, blackboards are well cared for. This situation illustrates that students assume that learning facilities in schools are very important so that together students and teachers take care of existing learning facilities. Likewise, learning facilities at home students have literature books to use when studying on their own.